2004
DOI: 10.1016/s0270-9295(04)00131-7
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of preeclampsia

Abstract: There have been many attempts to produce animal models that mimic the hypertensive disorders of pregnancy, especially preeclampsia, but most are incomplete when compared to the full spectrum of the human disease. This review assesses a number of these models, organized according to the investigators attempt to focus on a specific pathogenic mechanism believed to play a role in the human disease. These mechanisms include uterine ischemia, impairments in the nitric oxide system, insulin resistance, overactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 112 publications
0
42
0
3
Order By: Relevance
“…11 The combination of upright posture and uteroplacental ischemia may be necessary for manifestation of the full syndrome. 12 Chronic nitric oxide synthase inhibition in rats produces a pattern of change that resembles the symptoms of preeclampsia, and the preeclamptic-like response of rats with adriamycin nephropathy and hyperinsulinemia is associated with endothelial dysfunction. Vasoconstrictive prostanoids have been investigated by Kriston et al 13 Granger et al relied on reduced uterine perfusion to investigate the role of inflammatory cytokines, nitric oxides, and metabolites of arachadonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…11 The combination of upright posture and uteroplacental ischemia may be necessary for manifestation of the full syndrome. 12 Chronic nitric oxide synthase inhibition in rats produces a pattern of change that resembles the symptoms of preeclampsia, and the preeclamptic-like response of rats with adriamycin nephropathy and hyperinsulinemia is associated with endothelial dysfunction. Vasoconstrictive prostanoids have been investigated by Kriston et al 13 Granger et al relied on reduced uterine perfusion to investigate the role of inflammatory cytokines, nitric oxides, and metabolites of arachadonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Over 65 years ago, A. Randall demonstrated that interstitial crystals located at, or adjacent to, the papillary tip, Randall's plaques, were common in stone formers (2). He found that these crystals were composed not of calcium oxalate, the most common solid phase found in patients with nephrolithiasis, but of calcium phosphate (3). He believed that the calcium phosphate crystals formed in the papillary interstitium and then eroded into the urinary space, serving as a heterogeneous nucleation surface for calcium oxalate.…”
Section: Altered Angiogenic Balance Causes General Endothelial Dysfunmentioning
confidence: 99%
“…But, as of today, no satisfactory unifying hypothesis has emerged (1). The restricted occurrence of preeclampsia to humans and primates and the lack of a suitable animal model have hampered the understanding of its pathogenesis (3). In this issue of the JCI, S.E.…”
mentioning
confidence: 99%
“…The current generally acceptable pathophysiology of PE is that it is a two-stage disorder: at stage I (most likely during the late first trimester or early second trimester), there is a decrease in placental perfusion, which is secondary to abnormal migration of trophoblasts into maternal spiral arteries; of stage II (most likely during the early third trimester) of the maternal syndrome of PE, is secondary to systemic endothelial dysfunction (e.g., impairments in the nitric oxide system, overactivity of the autonomic nervous and/or renin-angiotensin systems, activation of a systemic inflammatory response, and activation of circulating proteins that interfere with angiogenesis) 21,22 . The link between reduced perfusion and the maternal syndrome is believed to be increased oxidative stress and/or an increased inflammatory response 23 .…”
Section: Pathogenesis Of Preeclampsiamentioning
confidence: 99%